2021
DOI: 10.1128/mbio.03146-20
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Catabolite Repression in Filamentous Fungi Is Regulated by Phosphorylation of the Transcription Factor CreA

Abstract: Filamentous fungi of the genus Aspergillus are of particular interest for biotechnological applications due to their natural capacity to secrete carbohydrate-active enzymes (CAZy) that target plant biomass. The presence of easily metabolizable sugars such as glucose, whose concentrations increase during plant biomass hydrolysis, results in the repression of CAZy-encoding genes in a process known as carbon catabolite repression (CCR), which is undesired for the purpose of large-scale enzyme production. To date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 66 publications
0
47
0
1
Order By: Relevance
“…Multiple phosphorylation sites of Cre1/CreA have been identified in N . crassa (Figure S1) and other filamentous fungi (de Assis et al, 2021; Horta et al, 2019) and characterized. However, only dephosphorylation on S6 and S211 was identified in response to cellobiose and Avicel (Table 1), and none of them were characterized in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple phosphorylation sites of Cre1/CreA have been identified in N . crassa (Figure S1) and other filamentous fungi (de Assis et al, 2021; Horta et al, 2019) and characterized. However, only dephosphorylation on S6 and S211 was identified in response to cellobiose and Avicel (Table 1), and none of them were characterized in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six serine residues (S262, S277, S288, S289, S312, and S319) in A. nidulans CreA were identified as phosphorylation sites by LC-MS analysis, and three of them (S289, S312, and S319) were phosphorylated only under conditions of growth in a glucose medium (Alam et al, 2017). Another recent study revealed six additional phosphorylation sites in A. nidulans CreA (S176, S268, S281, S284, T308, and S406; de Assis et al, 2021). The replacement of T308 with alanine significantly inhibited the nuclear accumulation of CreA-GFP.…”
Section: Nuclear Export-dependent Degradation Of Creamentioning
confidence: 99%
“…The replacement of T308 with alanine significantly inhibited the nuclear accumulation of CreA-GFP. In contrast, the replacement of S262 or S268 with alanine increased the nuclear localization of CreA-GFP under de-repressing conditions, although these CreA-GFP mutants were not detectable by western blotting under such conditions ( de Assis et al, 2021 ). Phosphorylation at S319 is lost upon the deletion of pkaA , which encodes a cAMP-dependent protein kinase, whereas CreA is not a direct target of this protein kinase ( Ribeiro et al, 2019 ).…”
Section: Carbon Catabolite Repression Of Hydrolytic Enzyme Genesmentioning
confidence: 99%
See 2 more Smart Citations